The law and the lady - Collins, Wilkie, 1824-1889 (Floating Press, 2010)
Valeria Woodville in The Law and the Lady (1875) must unravel the secrets of her husband's earlier life; she takes the law into her own hands and becomes one of the first woman detectives in fiction.